Inhibition of Fibroblast Activation Protein alpha (FAP-α) in Colorectal Cancer - Tabassum, Azwada (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Pharmacy, 2020.